Effectiveness of the SAVI Learning Model Assisted by Interactive Video on the Learning Outcomes of Fourth Grade Elementary School Students - Ariyani, Feri; Fakhriyah, Fina; Hilyana, F. Shoufika (FKIP - Universitas Riau, 2025)
This study aims to determine the differences in pretest and posttest scores in the Somatic, Auditory, Visual, Intellectual (SAVI) Learning Model assisted by interactive video on the learning outcomes of fourth-grade elementary school students. This research uses a quantitative research method with a one-group pretest-posttest design. The research was conducted by applying the SAVI learning model with interactive video assistance to the research subjects. The data analysis technique used is the paired sample T-test using IBM SPSS 26 software. The research sample consisted of 30 fourth-grade students at SD Negeri Pakem 01. The study results show a significant difference between the pretest and posttest scores of students after implementing the SAVI learning model assisted by interactive video, as indicated by the results of the paired sample T-test.